MODELING OF THE OPERATION OF FREE-SPACE OPTICAL COMMUNICATION UNDER THE EFFECTS OF RADIATION - Turovsky, A.; Blaghenny (Science-based technologies, 2021)
The article analyzes the operation of FSO receivers in the probable man-made disaster at a radiation-hazardous object and presents the mathematical model, which describes the FSO operation taking into account the possible effects of gamma radiation on the detection ability of the infrared input signal receiver.